PHYSICIAN BURNOUT LEVELS AND ASSOCIATED FACTORS IN THE COVID-19 PANDEMIC - Yilmaz, Sinan; Koşan, Zahide; Bilge Yerli, Ezel; Çınar Tanriverdi , Esra; İba Yılmaz , Sibel (Sanamed, 2023)
Introduction: Burnout, characterized by emotional exhaustion, depersonalization, and low personal accomplishment, is frequently observed in physicians. Aim: The purpose of this study was to determine burnout levels and associated factors in physicians during the pandemic. Material and Method: This cross-sectional study was performed online with 288 physicians from various fields in Erzurum. Sociodemographic questions and the Maslach Burnout Inventory represented the data collection tools. The data were collected online in May and June 2021. Statistical analysis: Descriptive statistics, Student’s t and ANOVA tests And Multiple ordinal logistic regression analysis were used. p values <0.05 were regarded as significant. Analysis was performed on SPSS 22. Results: Physicians’ mean emotional exhaustion, depersonalization, and personal accomplishment component scores were 20.1±8.3, 6.7±4.5, and 21.1±4.5, respectively. Analysis showed that 49.7% of physicians exhibited moderate-high emotional exhaustion, 35.8% high-moderate depersonalization, and 69.8% signs of low personal accomplishment. Job title, regret concerning selecting the medical profession, satisfaction with the working environment, number of additional monthly out-of-hours shifts worked, regular sporting activity, and assessment of the physical conditions in the working environment emerged as factors affecting burnout components at regression analysis. Conclusion: The participants’ burnout levels were high. The planning of effective interventions addressing individual and work-related factors with a holistic approach is essential to halt this rapidly growing epidemic.